Perancangan Mail Server dengan Menggunakan Exchange Server Studi Kasus di STMIK Bina Sarana Global - Hakim, Zainul; Hanafri, Muhammad Reza; Bayu, Kurniawan (JURNAL SISFOTEK GLOBAL, 2015)
Developments in technology and business needs in college STMIK Bina Sarana Global activity for the employees, faculty and students toward digital. As a means of supporting activities in college STMIK Bina Sarana Global activity staff employees, faculty and students currently use a public email domain so it does not represent the college STMIK Bina Sarana as campus-based Global IT. The system that is in use by the public at the college email STMIK Global Development Facility is not currently on the monitor so that the data can be confidential that is sent and received via email public becomes unsafe. Weak monitoring email turnover in college STMIK Global Development Facility will degrade the image of the campus. Therefore, in this paper will be implemented designing mail server using Exchange Server 2013 (local mail) by using the domain simulation using virtual machines. As for testing the design of the mail server using the mail send and receive mail. Based on the design concept of the mail server, it can be concluded the construction design destination mail server on STMIK Global Development Facility is to facilitate monitoring the entry and exit of mail in activities that occur on STMIK Global Development Facility, so as to overcome the problems that exist in the public mail which is currently in use.